Urban dendroflora of the Macedonia Park in the City of Skopje, North Macedonia - Shotaroska, Martina (Array, 2019)
Subject of research in this article is the urban dendroflora of the Macedonia Park, situated on about 50,000 m2 in the Macedonian capital city of Skopje, i.e., identification and presence of the recent woody plants. Thus, observed are morphological and ecological features of the woody plants and their current state in this urban environment. The investigation relates to a seven-year period (since the establishment of the Park in 2012 up to late 2019). After the field research and the inventorisation of the woody plants in the Park, 82 taxa were identified, represented in 1,318 individuals. Most represented tree species is the hybrid Platanus × hispanica Mill. ex Münchh. with 103 individuals (7.81% of the overall urban dendroflora). Most frequent tree including infraspecific taxa is Fraxinus excelsior L. (including F. e. ‘Globosa’, F. e. ‘Jaspidea’, and F. e. ‘Pendula’) with a total number of 146 individuals (11.08%). Concerning other growth form, the mini and small tree roses of hybrid Rosa Floribunda Group outnumber all ornamental woody species with 225 bushes (17.07%). Climbers are represented with 3 taxa (3.66% of identified taxa) in pergolas (Wisteria sinensis /Sims/ Sweet, Parthenocissus quinquefolia /L./ Planch.), and wire cage topiary (Hedera helix L.). Likewise, 87 individuals (6.60%) of 10 species (12.19%) occur as remnants of the greening in the past of which 3 species are used as a green core of a small sacral architecture: Cupressus sempervirens var. horizontalis (Mill.) Loudon (with 10 trees), Platycladus orientalis (L.) Franco (3), and Pinus nigra J.F.Arnold (1). In general, the urban dendroflora is properly selected and used for greening, although certain species and individuals are withering (e.g. Betula pendula ‘Youngii’, Juniperus scopulorum ‘Skyrocket’, F. e. ‘Jaspidea’) or unsuitably used for avenue and in small alpine-like garden.